2021
DOI: 10.1038/s41591-021-01310-z
|View full text |Cite
|
Sign up to set email alerts
|

Actionable druggable genome-wide Mendelian randomization identifies repurposing opportunities for COVID-19

Abstract: Drug repurposing provides a rapid approach to meet the urgent need for therapeutics to address COVID-19. To identify therapeutic targets relevant to COVID-19, we conducted Mendelian randomization (MR) analyses, deriving genetic instruments based on transcriptomic and proteomic data for 1,263 actionable proteins that are targeted by approved drugs or in clinical phase of drug development. Using summary statistics from the Host Genetics Initiative and the Million Veteran Program, we studied 7,554 patients hospit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(154 citation statements)
references
References 61 publications
(65 reference statements)
6
133
0
Order By: Relevance
“…This association has also been observed in other GWAS [ 15 , 17 ] but not all [ 16 ]. Several other putative genome-wide associations have been identified in individual studies with various approaches, including antiviral effectors OAS1, OAS2, OAS3; TYK2; IL10RB ; and ACE2 [ 16 , 17 , 19 ] (Table 1 ). Interestingly, these studies have not identified a significant association in the human leukocyte antigen (HLA) locus, although two targeted analyses of HLA types have reported significant associations with SARS-CoV-2 infection [ 20 , 21 ].…”
Section: Genome-wide Association Studies Of Severe Covid-19mentioning
confidence: 99%
“…This association has also been observed in other GWAS [ 15 , 17 ] but not all [ 16 ]. Several other putative genome-wide associations have been identified in individual studies with various approaches, including antiviral effectors OAS1, OAS2, OAS3; TYK2; IL10RB ; and ACE2 [ 16 , 17 , 19 ] (Table 1 ). Interestingly, these studies have not identified a significant association in the human leukocyte antigen (HLA) locus, although two targeted analyses of HLA types have reported significant associations with SARS-CoV-2 infection [ 20 , 21 ].…”
Section: Genome-wide Association Studies Of Severe Covid-19mentioning
confidence: 99%
“…A genetic instrument for IL-6R was found to be associated with a lower risk of hospitalization for COVID-19, suggesting the relevance of therapeutic inhibition of IL-6R, which has now been confirmed in clinical trials (Bovijn et al 2020; The WHO Rapid Evidence Appraisal for COVID-19 Therapies (RE-ACT) Working Group et al 2021). MR has also been used to systematically scan hundreds of druggable proteins to prioritize targets for drug trials, for example, highlighting OAS1 as a candidate for drug development (Gaziano et al 2021;Zhou et al 2021). Additional studies point toward host antiviral defense mechanisms and mediators of inflammatory organ damage as mechanisms underlying critical illness in COVID-19 (Pairo-Castineira et al 2021).…”
Section: Trends and Future Developmentsmentioning
confidence: 99%
“…A dysregulated type I interferon (IFN) system is typical of SLE (5)(6)(7). Type I IFNs are key components of the innate and adaptive immune responses to new pathogens, and their pivotal role in antiviral immunity is well established, including unbalanced inflammatory responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (8,9). Preliminary data suggest that patients with SLE do not have an increased risk of SARS-CoV-2 infection, or severe COVID-19, compared with the general population (2,10,11).…”
Section: Introductionmentioning
confidence: 99%